2017
DOI: 10.1186/s13195-017-0272-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cognitive outcome of Alzheimer’s disease and dementia with Lewy bodies: dual disease is worse

Abstract: BackgroundLongitudinal studies of dementia with Lewy bodies (DLB) are rare. Clinically, DLB is usually considered to worsen into Alzheimer’s disease (AD). The aim of our study was to compare the rate of the cognitive decline in DLB, AD, and the association of the two diseases (AD + DLB).MethodsUsing the Regional Network for Diagnostic Aid and Management of Patients with Cognitive Impairment database, which includes all the patients seen at all memory clinics (medical consultation and day hospitals) in four Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
(34 reference statements)
1
24
0
1
Order By: Relevance
“…Visual recognition memory, semantic fluency and ideomotor praxis are more severely impaired in DLB patients , who also show significantly lower scores on the tests of attention, executive function and constructional tasks . Episodic verbal memory is also worse in DLB than PDD, and the rate of cognitive decline is faster in DLB than PDD and AD . One study showed that the average annual decline in MMSE score in DLB is approximately two points in comparison with PDD (1.8) and AD (1.6) .…”
Section: Methodsmentioning
confidence: 99%
“…Visual recognition memory, semantic fluency and ideomotor praxis are more severely impaired in DLB patients , who also show significantly lower scores on the tests of attention, executive function and constructional tasks . Episodic verbal memory is also worse in DLB than PDD, and the rate of cognitive decline is faster in DLB than PDD and AD . One study showed that the average annual decline in MMSE score in DLB is approximately two points in comparison with PDD (1.8) and AD (1.6) .…”
Section: Methodsmentioning
confidence: 99%
“…The pattern of initial cognitive dysfunction differs between DLB and PDD [ 60 ], with greater deficiencies of attention, executive function, and constructive abilities, as well as significantly lower ratings in episodic verbal memory tasks, in DLB [ 61 , 62 ]. Further, the rate of cognitive decline is reportedly faster in DLB than in PDD and AD [ 63 , 64 ] (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Blanc et al 6 reported the frequency of dementia patients as 1000 AD (86.3%), 131 DLB (11.3%) and 28 dual diseases (2.4%). The ratio of DLB vs AD is 1:7.6, and the frequency of dual disease among total DLB is 0.7%.…”
Section: Discussionmentioning
confidence: 99%